2020
DOI: 10.1007/s10111-020-00642-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coherent, integrated, and context-dependent adaptable user interfaces on operators’ situation awareness, performance, and workload

Abstract: Nautical traffic management in The Netherlands is shifting from local traffic control to corridor traffic management. Current traffic management systems do not sufficiently support operators in perceptual and cognitive process to interpret and understand the large amounts of information needed for corridor traffic management. Newly developed user interface concepts aim to overcome deficiencies of current interface designs that insufficiently support situation awareness assessment. The effects of these new user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The studies by Chen et al (2014, 2015) show overall improvements in SA, the study by Selkowitz et al (2017) found improved SA for Level 2 and 3 SA (but did not report overall results), and the results from Skraaning and Jamieson (2021) and Roth et al (2020) show some mixed results depending on how transparency was implemented and which measurement instrument was used respectively. Still, having the information directly perceivable on the interface could reduce the burden on mental processing capacity by reducing the need for keeping multiple information elements in working memory (van Doorn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies by Chen et al (2014, 2015) show overall improvements in SA, the study by Selkowitz et al (2017) found improved SA for Level 2 and 3 SA (but did not report overall results), and the results from Skraaning and Jamieson (2021) and Roth et al (2020) show some mixed results depending on how transparency was implemented and which measurement instrument was used respectively. Still, having the information directly perceivable on the interface could reduce the burden on mental processing capacity by reducing the need for keeping multiple information elements in working memory (van Doorn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As good SA, without requiring excessive mental effort, increases the probability for good operator performance (Endsley, 1995; van de Merwe et al, 2012; van Doorn et al, 2021), we assessed those studies in which SA, mental workload, and performance were measured together. Five of the 17 studies measured these three variables in conjunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such roles may require shifting attention between one unit and another, or between one task and another, emphasising the need for rapid assessment of agent performance and 'to quickly get in-the-loop' (Porathe, Fjortoft, & Bratbergsengen, 2020, p. 3). Assuming that human-centred design principles are adequately applied in this study (Endsley et al, 2003;ISO, 2019), this study anticipates that the availability of information that supports transparency, in the form of SA knowledge directly perceivable on the CAGA system's interface, expedites the supervisor's attainment of SA (van Doorn et al, 2021). Therefore, it is hypothesized that users spend less time to comprehend the CAGA system's reasoning when this information is available (Kunze, Summerskill, Marshall, & Filtness, 2019;Roth, Schulte, Schmitt, & Brand, 2020) (see Table 1).…”
Section: Agent Transparency and Autonomous Shippingmentioning
confidence: 97%
“…Here, increased levels of transparency information may provide an additional information burden and the risk of overloading the operator with information that supports transparency is high, especially when increased information leads to display clutter (Moacdieh & Sarter, 2015a). However, despite risks of increased workload with agent transparency, recent studies have not found a clear relationship between these variables (Ezenyilimba et al, 2023;Loïck, Guérin, Rauffet, Chauvin, & Éric, 2023;, possibly because of the use of graphical symbols and integration of transparency information in task displays (Gegoff, Tatasciore, Bowden, McCarley, & Loft, 2023;van de Merwe, et al, 2024a;van Doorn, Horváth, & Rusák, 2021). Building on these findings, this study anticipates that when, first, information requirements are identified based on an iterative human-centred design approach (Endsley et al, 2003;ISO, 2019), second, symbology is developed based on context-specific industry standards (IEC, 2022), and third, transparency information is integrated in the primary task display (Skraaning & Jamieson, 2021;van Doorn et al, 2021), mental workload will not be affected by agent transparency (see Table 1).…”
Section: Agent Transparency and Autonomous Shippingmentioning
confidence: 99%